DESAIN DIOTRIK BERBASIS AR DALAM MENINGKATKAN LITERASI SAINS SISWA KELAS V SEKOLAH DASAR - Azizah, Umi Nur; Fatih, Mohamad; Wafa, Khoirul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study introduces the development of a digital learning environment in the form of an electric diorama (DIOTRIK) based on Augmented Reality (AR), designed using the theme Natural Scenery and Its Utilization to enhance science knowledge among fifth-grade elementary students. The research employed a Research and Development (R&D) approach, adapting the Borg and Gall model. The experimental design used in the field test was a One-Group Pretest–Posttest Design. Data were collected through interviews, surveys, experiments, and documentation. The results of the media validation showed that the diorama design was categorized as very valid by media experts with a score of 98%, and valid by material experts with a score of 73%, indicating that the developed product is highly feasible for use. The effectiveness of the learning environment was reflected in the posttest average score of 89.28 compared to the pretest average of 58.03. The N-Gain value of 0.782 falls into the high category (0.70 ? n ? 1.00). Thus, the use of visual aids such as the DIOTRIK AR diorama positively impacts students’ learning outcomes compared to learning without visual support.